HUKUMAN MATI TERHADAP TINDAK PIDANA KORUPSI DANA BANSOS PADA SAAT PANDEMI COVID-19 - Alvi Leo Saputra (Gapenas Publisher, 2022)
Corruption is an extraordinary crime whose eradication is carried out with a special institution, namely the Corruption Eradication Commission (KPK). During the COVID-19 pandemic, the Corruption Eradication Commission (KPK) carried out its task of carrying out arrest operations against several suspected corruption of social assistance funds. Corruption carried out during the Covid-19 pandemic emergency that had been determined by the President of Indonesia, Covid, was a certain condition that could result in the imposition of the death penalty, considering that Covid has also it was declared a non-natural disaster that had an impact on the number of poor people increasing and then the government implemented a special program to alleviate poverty but the funds were corrupted. Under these conditions, the researcher wants to examine the imposition of the death penalty on corruption in social assistance funds. This research is a normative juridical research. The results of the study state that corruptors can be sentenced to death according to the laws and regulations concerning the Eradication of Corruption Crimes